Cultural Orientation and Reporting Channels: Experimental Study of Whistleblowing Intentions - Romaito Situmeang; Intiyas Utami; I Gede Cahyadi Putra (The Indonesian Journal of Accounting Research, 2020)
Individualism refers to personal interests while collectivism refers to collective interests. Formal and informal reporting channels are accesses to report wrongdoings. This research aims to test the causality effect between cultural orientation and whistleblowing intention. The second objectives is to test the causality effect between reporting channel to whistleblowing intention. The third objectives is to examines the interaction effect between cultural orientation and reporting channel to whistleblowing intention. These research use 2x2 between subjects’ factorial design. The manipulation of this research is cultural orientation (individualism and collectivism) and reporting channels (formal and informal). The subjects in this research are accounting students of two private universities in Central Java and Bali. The variable measured is whistleblowing intention. The results of the main effects test show that the cultural orientation has an effect on the intention to complain about fraud. The testing of other main effects shows that the reporting channel has an effect on the whistleblowing intention. Testing the interaction effect shows that cultural orientation influences the intentions of whistleblowing intention depending on the reporting channels provided.